Associações de classe industriais na sociedade pós-industrial: um estudo de caso no Setor Eletroeletrônico - Galvao, Paulo Sergio de Almeida (2002)
Industrial societies are turning into informationai societies because of the increasing technoiogicai advances mostly when reiated to ITC. The aims of ABINEE - the Brazii s most important association at federal and regional levei for companies in the electrical and electronics sector - have been examined through the body strategicai analysis and besides that, a research took piace in order to focus practides developed for more than 50 associations and federations of several countries as weii as their missions, scopes and services, developed in order to compiy with demands of their members within this society of information, to compare with the deveioped by ABINEE, checking ifABINEE does it iike them. it was verified that ali of them aim the defense, the promotion and the representation of both the professional and coilective interests of its members. These industries associations and federations offer the sarne services, with very few differences among them. AB1NEE offers a broad raflge of practicai sources of assistance, and direct benefit to every mernber on a daily basis, in a levei as observed worid wide. in conciusion, ABINEE consequentiy, offers its services exactly iike other industries associations and federations and is in accordance with the state of the art. Some suggestions were formulated with the purpose of providing means developing new studies about these issues, which have not been enough studied